Anomalous branching of the middle meningeal artery from the basilar artery: a systematic review - Salman, Maryam A.; Mallah, Saad I.; Almadi, Faris Soloman; Almayman, Talal; Corbally, Martin (Frontiers in Neurology, 2024)
Background Anomalous origin of the middle meningeal artery (MMA) from the basilar artery is a rare congenital neurological variant that has been detected in both children and adults with diagnoses ranging from intracranial haemorrhage to ependymoma. This review aims to investigate the anatomical course of an anomalous basilar-middle meningeal artery and its clinical presentation. Methods A systematic search was performed in PubMed using the keywords (middle meningeal artery) and (basilar artery). Ninety-four papers were identified, of which seven were included. One paper was further identified through cross-referencing. Results The average age of presentation was 43 years with a male predominance (7/9). In most cases, the MMA arose between the superior cerebellar artery and the anterior inferior cerebellar artery (8/9) (versus 1 case between the anterior inferior cerebellar artery and the posterior inferior cerebellar artery). The anomaly mostly presented on the left side (6/11), but was bilateral in one case. Most of the cases showed a pontine artery branching from the basilar artery arising 5 mm to 10 mm proximal to the superior cerebellar artery, which would then assume the trajectory of the MMA. In three cases, the vessel increased in calibre near the trigeminal ganglion. Foramen spinosum absence in the anomalous side was noted in 3/6 of the patients. Conclusion To avoid unexpected complications during neurosurgical and neuroradiointerventional procedures, it is essential to have a clear understanding of the anomalous routes of the MMA. This is especially important when it proves to be the only available route for embolization.